2009
DOI: 10.1007/s00134-009-1466-8
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of delirium is severely underestimated in the ICU during daily care

Abstract: Objective: Delirium is associated with prolonged intensive care unit (ICU) stay and higher mortality. Therefore, the recognition of delirium is important. We investigated whether intensivists and ICU nurses could clinically identify the presence of delirium in ICU patients during daily care. Methods: All ICU patients in a 3-month period who stayed for more than 48 h were screened daily for delirium by attending intensivists and ICU nurses. Patients were screened independently for delirium by a trained group of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
188
3
26

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 321 publications
(224 citation statements)
references
References 22 publications
7
188
3
26
Order By: Relevance
“…A previous study found that clinicians are unable to diagnose 70% of cases of delirium when a validated delirium screening tool is not used. 18 Therefore, we did not attempt to quantify the incidence of delirium using progress notes or diagnosis codes, as this incidence would be falsely low and unreliable. Our hospital is currently improving the culture of awareness of delirium, and efforts are being made to establish and improve routine screening for delirium in both the acute care and critical care setting.…”
Section: Limitationsmentioning
confidence: 99%
“…A previous study found that clinicians are unable to diagnose 70% of cases of delirium when a validated delirium screening tool is not used. 18 Therefore, we did not attempt to quantify the incidence of delirium using progress notes or diagnosis codes, as this incidence would be falsely low and unreliable. Our hospital is currently improving the culture of awareness of delirium, and efforts are being made to establish and improve routine screening for delirium in both the acute care and critical care setting.…”
Section: Limitationsmentioning
confidence: 99%
“…Tilnaermingen var imidlertid usystematisk og preget av subjektive vurderinger. Også dette er et bilde av praksis som stemmer med tidligere forskning; sykepleiere bruker metoder som nevrologisk undersøkelse, observasjon og samtale med pasienten for å vurdere om pasienten har delirium (2,7,35,36). Både våre funn og disse tidligere studiene viser at sykepleiere vektlegger orienteringsevne, avvikende atferd, bevissthet, pupiller, agitasjon og evne til å følge oppfordring.…”
Section: Andre Studierunclassified
“…Konsekvensene av delirium hos intensivpasienten er betydelige i form av økt døde-lighet, økt liggetid på respirator og i sykehus, og langtidsplager som angst og konsentrasjonsvansker for pasienten (3)(4)(5)(6). Det er derfor et stort problem at delirium ikke blir oppdaget hos denne pasientgruppen (2,(7)(8)(9)(10).…”
Section: Introduksjonunclassified
See 1 more Smart Citation
“…Once thought to be an inevitable byproduct of sepsis and severe illness, delirium is now known to be a form of acute brain dysfunction associated with higher mortality [2][3][4], increased length of hospital stay [5], increased costs [6], and long-term cognitive impairment [7][8][9][10]. The development of valid and reliable instruments to assess delirium has resulted in better recognition of delirium [11,12], although it continues to be under-recognized [13]. The focus of delirium research has been extended to include pharmacological and nonpharmacological strategies to prevent and minimize the duration of delirium.…”
Section: Introductionmentioning
confidence: 99%